The regulatory control over radiation sources: the Brazilian experience and some lessons learned from industrial applications (Brazilian Journal of Radiation Sciences (BJRS), 2019)
This study gives an overview of the activities of the National Commission of Nuclear Energy (CNEN), as the Brazilian nuclear regulatory authority. These activities are described, especially those related to management of orphan sources and radioactive material in scrap metal considering the actions already put into place by CNEN during the licensing and controlling of radioactive sources in the industry and other facilities. In Brazil, there is not yet an effective system for controlling the scrap metal and recycling industry, thus a coordinated approach to achieve a harmonized and effective response with the involvement of third parties is needed, especially the metal industries and ores facilities. These practices call for stringent regulatory control, in order to reduce the occurrence of orphan sources, and consequently, radioactive material appearing in scrap metal. Some challenges of managing the national radiation sources register systems will be discussed, in order to cover effectively all the radiation source history (in a ‘from the cradle to the grave’ basis), and the dynamic maintenance and update of these data. The main industrial applications considered in this work are those dealing with constant movement of sources all over the country, with geographical issues to be considered in the managing and controlling actions, such as gammagraphy and well-logging.  This study aims to identify and promote good practices to prevent inadvertent diversion of radioactive material, taking into account existing international recommendations and some lessons learned in national level.